The Paradox of E-Office Adoption in Indonesian Public Service with 24.000 Apps: Innovation or Prestige? - Safira, Nadia; Hanan, Haris (Jurnal Sosial Humaniora, 2025)
This study examines the adoption process of e-office systems in Indonesian government agencies, driven by the ZI WBK/WBBM competition aimed at promoting corruption-free bureaucratic areas. The research reveals that during the confirmation stage of e-office implementation, the focus shifted from assessing true innovation to merely obtaining the WBK/WBBM designation. This emphasis on the title undermines the core goal of e-office— improving public service delivery through e-governance. The study identifies five key stages in the adoption process: knowledge acquisition, persuasion, decision-making, implementation, and confirmation. It suggests that stakeholders may prioritize the incentive of the ZI title over a deeper understanding of the technology’s benefits. Additionally, conflicting regulations present challenges that hinder successful implementation. The study concludes that a revised approach is needed, one that prioritizes user experience, public service improvement, and the core functionalities of the eoffice. By focusing on these elements, stakeholders can ensure the system enhances government transparency and efficiency. This qualitative research uses case-based analysis, drawing on interviews with government employees and IT personnel involved in the ZI WBK/WBBM implementation.